Production of cellulose and microcellulose from pineapple leaf fibre by chemical-mechanical treatment - Surenthiran, Gnanasekaran; Y. Y., Li; Jun Haslinda, Shariffuddin; Noor Ida Amalina, Ahamad Nordin (IOP Publishing, 2020)
Pineapple leaf fibre (PALF) is major waste from pineapple cultivation with high cellulose content that exhibits superior mechanical properties. In this study, chemical-mechanical treatments were conducted to produce cellulose and microcellulose. For alkali and steam treatment, PALF treated with 5 wt% sodium hydroxide solution and steamed in an autoclave at temperature of 121 °C and pressure of 21 psi. Next, the PALF was bleached with 5 wt% sodium chlorite. Continued with acid hydrolysis with 3.5 M and 7.5 M hydrochloric acid to produce cellulose. For, the mechanical treatment which involved homogenization and ultrasonication to produce the microcellulose, the ultrasonication was varied for 30 and 60 min. The samples were analysed by Scanning Electron Microscopy, Thermal Gravimetric Analysis and Fourier Transform Infrared Spectroscopy (FTIR) to study surface morphology, thermal stability and functional group respectively. The results showed that ABAHU60 with alkali treatment, bleaching, acid hydrolysis, homogenization and ultrasonication of 60 min exhibits excellent thermal stability and surface morphology, where the maximum degradation temperature occurs at 349 °C, which is a 5% improvement compare to untreated fibre. Its surface is smoother without impurities, with a loose structure and reduce diameter of fibre.